Kindergarten Resource Pack Understanding the world - The city school (Lahore,Pakistan. The city school)
The Kindergarten Resource Pack for "Understanding the World" in The City School curriculum helps young learners explore their surroundings and develop curiosity. It introduces basic concepts of science, nature, community, and technology through activities and discussions. The pack encourages observation, questioning, and exploration to build a deeper connection with the world. It aims to foster critical thinking and an appreciation for the environment.
The Kindergarten Resource Pack for "Understanding the World" in The City School curriculum helps young learners explore their surroundings and develop curiosity. It introduces basic concepts of science, nature, community, and technology through activities and discussions. The pack encourages observation, questioning, and exploration to build a deeper connection with the world. It aims to foster critical thinking and an appreciation for the environment.